An aerosol formulation of R-salbutamol sulfate for pulmonary inhalation - Xuemei Zhang; Qing Liu; Junhua Hu; Ling Xu; Wen Tan (Elsevier, 2014)
An aerosol formulation containing 7.5 mg of R-salbutamol sulfate was developed. The aerosol was nebulized with an air-jet nebulizer, and further assessed according to the new European Medicines Agency (EMA) guidelines. A breath simulator was used for studies of delivery rate and total amount of the active ingredient at volume of 3 mL. A next generation impactor (NGI) with a cooler was used for analysis of the particle size and in vitro lung deposition rate of the active ingredient at 5 °C. The anti-asthmatic efficacy of the aerosol formulation was assessed in guinea pigs with asthma evoked by intravenous injection of histamine compared with racemic salbutamol. Our results show that this aerosol formulation of R-salbutamol sulfate met all the requirements of the new EMA guidelines for nebulizer. The efficacy of a half-dose of R-salbutamol equaled that of a normal dose of racemic salbutamol.